The Role of Price as a Moderating Variable in the Influence of Product and Service Quality on Repurchase Intention - Br Ginting, Litka Tiadoraria; Ginting, Sugianta Ovinus; Wijaya, Vinny; Arifhienta, Fenysha (ProBisnis : Jurnal Manajemen, 2024)
This research aimed to determine and analyze the influence of product quality and service quality on repurchase intention with price as a moderating variable for Janji Jiwa Center Point Medan coffee. In this research, sampling techniques purposive sampling used, method non probability sampling, and the total number of samples was 113 samples. The questionnaire that has been filled out by the respondent will then be processed using PLS (Partial Least Square). The results of the analysis show that product quality and price influence repurchase interest, while service quality does not influence repurchase interest. Product quality and price influence customer satisfaction, while service quality has no influence on customer satisfaction. Price is unable to moderate the influence of viable product quality and service quality on repurchase interest in Janji Jiwa Center Point Medan coffee. ResultsR-square adjusted 1 is 0.490, meaning that the repurchase interest variable can be explained by product quality, service quality and price by 49%, while 51% is explained by other variables not examined in this research.